Analysis of Nepenthes Hybrids in Taratak Hill, Pesisir Selatan Sumatera Barat by RAPD Technique - Weni Enjelina; Mansyurdin Mansyurdin; Tesri Meideliza (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2018)
The Study about Analysis of Nepenthes Hybrids in Taratak Hill, Pesisir Selatan Sumatera Barat by RAPD Technique had been conducted from May until November 2011. The study was done to prove natural hybrids of Nepenthes by RAPD technique and to determine the relationship of natural hybrids of Nepenthes with both parental. The research method is survey and observation. Isolation of DNA carried by CTAB method with modifications and amplification carried out by PCR. Hybrids and parental relationship was obtained from Jaccard similarity coefficient and displayed in a Dendogram (family tree) and PCO analysis to look genetic variation was processed with the program PAST 2.10. Proof of the natural hybrid N. ampullaria × N. mirabilis can be done by the RAPD technique using the primers OPA 15, OPK 16, OPK 19 and OPP 15. Natural hybrids between N. ampullaria × N. gracilis using the primers OPA 15, OPK 19 and OPP 15. The eighth of natural hybrids N. ampullaria × N. mirabilis were closer to N. mirabilis, while both natural hybrids N. ampullaria × N. gracilis closer to the N. Ampullaria.